2021
DOI: 10.3390/nano11123402
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Nanomaterials for Arterial Embolization and Hyperthermia of Parenchymal Organs Tumors: A Review

Abstract: Magnetic hyperthermia (MH), proposed by R. K. Gilchrist in the middle of the last century as local hyperthermia, has nowadays become a recognized method for minimally invasive treatment of oncological diseases in combination with chemotherapy (ChT) and radiotherapy (RT). One type of MH is arterial embolization hyperthermia (AEH), intended for the presurgical treatment of primary inoperable and metastasized solid tumors of parenchymal organs. This method is based on hyperthermia after transcatheter arterial emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 130 publications
(233 reference statements)
0
5
0
Order By: Relevance
“…In addition, if hyperthermic heating of cells is insufficient, polymer coatings with higher critical temperatures can also be designed to release endotoxins by heating the particles with an alternating magnetic field, thereby providing additional targeted killing for drug delivery ( 96 , 97 ).…”
Section: Practical Application Of Af Treatment Methods Based On Nano ...mentioning
confidence: 99%
“…In addition, if hyperthermic heating of cells is insufficient, polymer coatings with higher critical temperatures can also be designed to release endotoxins by heating the particles with an alternating magnetic field, thereby providing additional targeted killing for drug delivery ( 96 , 97 ).…”
Section: Practical Application Of Af Treatment Methods Based On Nano ...mentioning
confidence: 99%
“…Magnetic nanomaterials with MR imaging capabilities could enhance the efficacy of liver chemoembolization ( Pouponneau et al, 2014 ). Studies have shown that magnetic nanomaterials were used for hyperthermia under the stimulation of an external magnetic field ( Kazantseva et al, 2021 ). At the same time, the specific modification of nanomaterials not only improved the specificity and effect of treatment but also reduced the damage to surrounding tissues ( Patra et al, 2018 ).…”
Section: The Advantage Of the Imageable Nanomaterialsmentioning
confidence: 99%
“…Typically, SPION emulsions in lipiodol or its derivatives are used for therapeutic processes. Temperatures in the range of 41–45 °C were obtained during previously published studies [ 15 ]. Recently it has been discovered that external ionizing radiation in combination with magnetic hyperthermia has a significantly greater (synergetic) effect on killing various cancer cells than using the two methods separately [ 16 ].…”
Section: Introductionmentioning
confidence: 99%